Posterior reversible encephalopathy syndrome and association with systemic lupus erythematosus. (October 2016) - Ferreira, TS; Reis, F; Appenzeller, S
Introduction: Posterior reversible encephalopathy syndrome (PRES) is a neurological complex disorder with many clinical associations and causative factors. It is important to recognize this condition because early diagnosis and treatment usually result in its complete resolution, radiological imaging becoming the key for the correct diagnosis. Methods: We retrospectively reviewed charts and magnetic resonance imaging findings in the University of Campinas from January 2005 to July 2015, selecting three cases of patients with systemic lupus erythematosus syndrome who developed PRES, for whom risk factors, characteristics, magnetic resonance imaging findings and neurological resolution were analyzed. We also conducted a review of the English-language literature. Results: The three cases had neurological symptoms like acute onset of headache, altered mental status, cortical blindness and seizures. Brain magnetic resonance imaging demonstrated posterior cortical and white matter alterations involving posterior brain territories, which were more conspicuous on T2-weighted and fluid-attenuated inversion recovery . Spectroscopy, diffusion-weighted imaging and susceptibility-weighted imaging were also important for neuroradiological evaluation. Immunosuppressive drugs were taken in all cases. Partial clinical and radiological recovery was observed in two cases, and complete resolution was observed in the third patient. Literature review: We found 52 cases of PRES in systemic lupus erythematosus patients. Almost all patients were women 94%, ranging from 8 to 62 years old. Posterior brain territory involvements were found in 98% of patients. Hemorrhagic complications involved 26% of patients, becoming a risk factor for clinical sequels. The total percentage of patients with no complete resolution of radiological findings on follow-up images was 27.5%. Discussion: In patients with autoimmune disorders, endothelial dysfunction may occur secondary to autoimmunity and the use of cytotoxic drugs, supposedly facilitating the occurrence of more severe PRES. The hypothesis that patients with autoimmune diseases have a propensity to develop non-reversible lesions has been raised.